Dietary intakes of professional Australian football league women`s (AFLW) athletes during a preseason training week - Jenner, S. L.; Devlin, B. L.; Forsyth, A. K.; Belski, R. (Journal of Science and Medicine in Sport, 2019)
Objectives: In 2016 the Australian football league introduced the first women`s league, integrating part-time female athletes into the professional sporting environment. This study aims to assess the dietary intakes of professional Australian football league women`s (AFLW) athletes to highlight key focus areas for nutrition and additionally provide nutrition recommendations for dietitians working with these athletes. Design: Cross-sectional study. Methods: Dietary intake data was collected from 23 players from the same club competing in the Australian football league women`s, during a preseason week. Dietary intakes were assessed using three day estimated food records. Results: Majority of athletes did not meet recommendations for carbohydrate (96%, n = 22), iron (87%, n = 20) and calcium (61%, n = 14). In comparison, majority of athletes met protein (74%, n = 17) and fat (78%, n = 18) recommendations. No significant difference was found in energy intake on main training, light training and recovery days (p > 0.05). Energy and carbohydrate intakes reported by AFLW athletes (1884 ± 457 kcal day-1 and 2.7 ± 0.7 g kg-1 day-1) were consistent with values reported in previous studies that included professional female athletes. Conclusions: This research highlights that further exploration of the factors that influence dietary intake is required to support athletes to meet energy and carbohydrate recommendations required for desired training and performance outcomes.